Recuperação de pasto de capim marandu com cinza vegetal : características nutricionais - Schlichting, Alessana Franciele (2018)
The destination of industrial waste from the combustion of vegetal biomass, the wood ash, is becoming a problem in Brazil. The objective of this study was to evaluate the nutritional characteristics of the pasture undergoing recuperation submitted to doses of wood ash and management of ash application in the soil. The experiment was carried out in the field, in degraded Marandu grass pasture, in a stripplot design in 6 x 2 factorial scheme, which corresponded to six wood ash doses (0, 3, 6, 9, 12 and 15 t ha-1) and two treatments of application of the wood ash (superficial, not incorporated and incorporated to the soil, with light grid), with four replications. The experiment was conducted in two consecutive years and the evaluations carried out in the rainy season each year. The leaves were evaluated: the chlorophyll index (SPAD index), concentration and accumulation of nitrogen, phosphorus, potassium, calcium, magnesium and sulfur; apparent nitrogen, phosphorus and potassium recovery; nutritional index of nitrogen, phosphorus and potassium. The data were submitted to analysis of variance and, when significant (p≤0.05), analyzed by the Tukey test for qualitative variables (application managements) and regression analysis for quantitative variables (doses of vegetal ash), both with probability statistic up to p ≤0.05 of error, using the statistical software SISVAR. The ash was also verified as a corrective and source of phosphorus and potassium for the soil. It can be verified that the vegetal ash helps in the recovery of the pasture, optimizing the nitrogen absorption and providing essential nutrients to the development of the recovering Marandu grass. The application of 12 to 15 t ha-1 plant ash doses is responsible for the maximum concentration and accumulation of nitrogen, phosphorus, potassium, calcium, magnesium and sulfur in the pasture. The management of soil ash incorporation in the soil influenced more the absorption of macronutrients than the application of ash on the surface. The dose of vegetable ash to be applied will depend intrinsically on the value of its relative total neutralization power and its chemical composition, which should neutralize the soil acidity and provide the adequate amount of nutrients for the crop.